2020
DOI: 10.2147/ijn.s242490
|View full text |Cite
|
Sign up to set email alerts
|

<p><sup>99m</sup>Tc Radiolabeled HA/TPGS-Based Curcumin-Loaded Nanoparticle for Breast Cancer Synergistic Theranostics: Design, in vitro and in vivo Evaluation</p>

Abstract: Background: Emerging cancer therapy requires highly sensitive diagnosis in combination with cancer-targeting therapy. In this study, a self-assembled pH-sensitive curcumin (Cur)loaded nanoparticle of 99m Tc radiolabeled hyaluronan-cholesteryl hemisuccinate conjugates (HA-CHEMS) and D-a-tocopheryl polyethylene glycol succinate (TPGS) was prepared for breast cancer synergistic theranostics. Materials and Methods: The synthesized amphiphilic HA-CHEMS conjugates and TPGS self-assembled into Cur-loaded nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…The pH-responsive drug release could be attributed to the presence of CHEMS in the hybrid-liposome, which would be protonated and change the structure in an acidic environment [ 65 ]. This would result the prepared NPs unstable at acidic environments, accelerating the release of FTY720.…”
Section: Resultsmentioning
confidence: 99%
“…The pH-responsive drug release could be attributed to the presence of CHEMS in the hybrid-liposome, which would be protonated and change the structure in an acidic environment [ 65 ]. This would result the prepared NPs unstable at acidic environments, accelerating the release of FTY720.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, no biochemical modifications or structural damage were observed in the liver and kidneys ( 40 ). Huang and co-workers ( 48 ) encapsulated curcumin in pH-sensitive polymeric NPs and showed a significant reduction in tumor volume followed by increased survival time ( Table 1 ) ( 48 ). Internalization of NPs can be mediated or not by active targeting ligands (depending on the mechanism triggered), and it occurs mainly through endocytosis pathways where the main mechanisms comprise a) clathrin-mediated endocytosis; b) caveolae-mediated endocytosis, for NPs up to 200 nm; c) macropinocytosis; and d) other clathrin and caveola-independent endocytosis for NPs with sizes between 250 nm and 3 µm ( 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle arrest by free curcumin has also been described and is potentially associated with its antiproliferative effects ( 74 ). Regarding the antitumor mechanisms reported in the included studies, Cur-NPs were shown to induce at least tumor apoptosis, necrosis, and/or cell proliferation blockage in in vivo breast cancer models ( 26 , 28 , 30 , 34 , 36 , 37 , 40 , 41 , 45 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang and colleagues [154] used membrane dialysis to fabricate self-assembled 99mTcradiolabeled CUR-NPs with HA-cholesteryl hemisuccinate conjugates and D-a-TPGS. The NPs (144 nm, −21.25 ± 1.66 mV, 84.0 ± 5.0% EE) inhibited 4T1 cell growth by twofold compared CUR (IC 50 values: 38 µg/mL vs. 77 µg/mL).…”
Section: Radiolabeled Npsmentioning
confidence: 99%